Grundtvigs sang-værk. Sjette bind, hefte 1 - Johansen, Steen (Grundtvig-Studier, 1957)
<span lang="EN-US" style="color: black; font-family: "Verdana","sans-serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA;">Grundtvigs Hymns , Vol. VI, Part I. Variant Readings and Notes on Vols. I & II. Det Danske Forlag (The Danish Publishing Co.), 1956. 180 pages.<span lang="EN-US" style="color: black; font-family: "Verdana","sans-serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA;"> <span lang="EN-US" style="color: black; font-family: "Verdana","sans-serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA;">By Steen Johansen.<span lang="EN-US" style="color: black; font-family: "Verdana","sans-serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA;"> <span lang="EN-US" style="color: black; font-family: "Verdana","sans-serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA;">The new edition of N. F. S. Grundtvig’s hymns, which was begun in 1944, has now reached its sixth and last volume, which contains only variant readings and explanatory notes, etc., on the preceding volumes. However, owing to the extent of the material it has been decided to publish the volume in three parts of numbers, of which up to the present the first has been published (in 1956), containing variant readings and notes on the first two volumes. <span lang="EN-US" style="color: black; font-family: "Verdana","sans-serif"; font-size: 12pt; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: DA;">The whole of this edition of the hymns, which is in charge of a commission under the leadership of the Reverend Uffe Hansen, has this peculiarity, that the first five volumes give only the text, while all the variant readings, explanations, etc., are given together in the final volume. In the reviewer’s opinion, it would certainly have been better if the variant readings had been printed in connection with each hymn; more space could thus have been gained for explanatory notes, which would have been of advantage to the edition. In preparing the list of variant readings all the various manuscripts have been used, in contradistinction to earlier editions. This in itself is sufficient to ensure that the present edition makes all previous ones of date. Much work has also be done on the investigation of the sources of Grundtvig’s translations of hymns, and, in addition, there are explanations of uncommon words, and references to Biblical passages in the hymns and to the literature on the subject of Grundtvig’s hymns. With all these qualities, this volume of notes marks a great step forward in Danish research on Grundtvig’s writings. Only now have Grundtvig’s hymns been published in a scholary form suited to our own time.